Key Structural Features of Azanaphthoquinone Annelated Pyrrole Derivative as Anticancer Agents Based on the Rational Drug Design Approaches. Issue 5 (11th June 2013) - Kamsri, Pharit; Punkvang, Auradee; Pongprom, Nipawan; Srisupan, Apinya; Saparpakorn, Patchreenart; Hannongbua, Supa; Wolschann, Peter; Pungpo, Pornpan
Abstract Azanaphthoquinone annelated pyrrole derivatives have been developed and synthesized with a continuous attempt to develop novel DNA intercalating agents as anti‐cancer compounds with lower organ toxicity. With the remarkable antiproliferative activity of synthesized azanaphthoquinone annelated pyrrole derivatives, a structurally novel scaffold of these compounds is appropriated for further development of novel anti‐cancer agents. Therefore, in the present study, 3D QSAR study (CoMSIA) was applied on 28 azanaphthoquinone annelated pyrrole derivatives to evaluate the structural requirement of these compounds. The resulting CoMSIA model is satisfied with r2 of 0.99 and q2 of 0.65. The interpretation of CoMSIA contours reveals the significant importance of steric, electrostatic, hydrophobic and hydrogen acceptor descriptors on the activities of azanaphthoquinone annelated pyrrole derivatives. Remarkably, the structural requirement of six substituent positions on the azanaphthoquinone annelated pyrrole scaffold was elucidated here. This result is the useful concept for design of new and more active azanaphthoquinone annelated pyrrole derivatives. Moreover, MD simulations using AMBER program were performed to model the binding of azanaphthoquinone annelated pyrrole derivatives in the intercalation site of the DNA duplex. Based on MD simulations, the information in terms of ligand‐DNA interaction, complex structure and binding free energy was provided in this work. Therefore, the integrated results are informative for further modification of azanaphthoquinone annelated pyrrole scaffold leading to gain novel azanaphthoquinone annelated pyrrole derivatives possessing better antiproliferative activity.